Iron-tetracyanobenzene complex derived non-precious catalyst for oxygen reduction reaction. (20th April 2015) - Choi, Ja-Yeon; Higgins, Drew; Jiang, Gaopeng; Hsu, Ryan; Qiao, Jinli; Chen, Zhongwei
Abstract: Non-precious metal oxygen reduction reaction (ORR) catalysts were prepared by pyrolyzing a carbon supported complex consisting of iron acetate coordinated with 1, 2, 4, 5-tetracyanobenzene (TCNB) in an iron phtalocyanine-like polymer arrangement. The effect of heat treatment temperature is systematically investigated from 700 to 1000 °C, with ORR activity investigated by half-cell electrochemical evaluation in 0.1 M HClO4 . The highest ORR performance is obtained for the sample heat treated at 1000 °C, with this sample demonstrating high (>98%) selectivity towards the efficient 4 electron reduction mechanism, comparable with some of the best non-precious metal catalysts reported to date. The physical and surface properties of the prepared catalysts were investigated by high-resolution transmission electron microscopy (TEM), fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), thermogravimetric analysis (TGA) and BET surface area analysis. After heat treatment, a thin (<10 nm) coating was observed on the surface of the carbon supports, attributed to residual species remaining from the heat treated precursor complex that provide the source of ORR activity.